Partisipasi Politik Pemilih Perempuan Desa Adat Sangket dalam Pemilukada Kabupaten Buleleng Tahun 2017 - Surya Mahadewa, I Gusti Ngurah Agung; Erviantono, Tedi; Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2022)
This study aims to find out what causes the low Political Participation of Sangket Traditional Village Women Voters in the Buleleng Regency Election 2017. The research is framed using the symbolic interaction theory of Herbert Mead. The research method used is a descriptive qualitative method using primary data and secondary data, because it describes the causes of the low Political Participation of Women Voters in Sangket Traditional Village in the 2017 Buleleng Regency General Election. The results of the research are: first, the low political participation of women due to Voting day coincided with Piodalan Day at Kahyangan Tiga Temple in Sangket Traditional Village, which made the women choose ngayah instead of voting. Second, the strength of the incumbent candidate and the lack of understanding of elections are factors that cause the low Political Participation of the Sangket Traditional Village Women Voters in the 2017 Buleleng Regency Election.